Antifungal Activity of the Biphosphinic Cyclopalladate C7a against Candida albicans Yeast Forms In Vitro and In Vivo - Muñoz, Julian E.; Rossi, Diego C. P.; Ishida, Kelly; Spadari, Cristina C.; Melhem, Marcia S. C.; Garcia, Daniel M.; Caires, Antonio C. F.; Taborda, Carlos P.; Rodrigues, Elaine G. (Frontiers in Microbiology, 2017)
Vulvovaginal and invasive candidiasis are frequent conditions in immunosuppressed individuals caused by Candida albicans and non-albicans Candida spp. Fluconazole and Amphotericin B are the main drugs used to fight the infection. However, resistance to fluconazole and other azole antifungal drugs is an important clinical problem that encourages the search for new therapeutic alternatives. In this work, we evaluate the antifungal activity of the biphosphinic cyclopalladate C7a in the in vitro and in vivo model. Our results showed fungicidal activity, with low values of minimal inhibitory concentrations and minimum fungicidal concentrations, even for fluconazole and/or miconazole resistant Candida isolates. Fluorescence microscopy and transmission electron microscopy revealed that the compound was able to inhibit the formation of hyphae/pseudohyphae and, moreover, promoted morphological alterations in cellular organelles and structures, such as disruption of cell wall, apparent mitochondrial swelling, chromatin marginalization into the nuclei and increased numbers of electron-lucent vacuoles. C7a significantly decreased the biofilm formation and reduced the viability of yeast cells in mature biofilms when tested against a virulent C. albicans strain. In vivo assays demonstrated a significant decrease of fungal burden in local (vaginal canal) and disseminated (kidneys) infection. In addition, we observed a significant increase in the survival of the systemically-infected animals treated with C7a. Our results suggest C7a as a novel therapeutic agent for vaginal and disseminated candidiasis, and an alternative for conventional drug-resistant Candida.